PENGARUH EKSTRAK KULIT JERUK KALAMANSI TERHADAP PERTUMBUHAN BAKTERI SALMONELLA TYPHI DAN SUMBANGANNYA PADA PEMBELAJARAN BIOLOGI SMA - Astri Indah Lestari; Khoiron Nazip; Riyanto Riyanto (BIO-EDU: Jurnal Pendidikan Biologi, 2022)
Kalamansi orange (Citrus microcarpa Bunge.) has the potential as a source of antimicrobials because the skin of the fruit contains flavonoid compounds, tannins, and alkaloids which have been shown to be able to inhibit the growth of gram-negative bacteria. This study aimed to obtain information on the effect of ethanolic extract of kalamansi orange peel (C. microcarpa Bunge.) on the growth of Salmonella typhi bacteria land the minimum inhibitory concentration of ethanolic extract of kalamansi orange peel (C. microcarpa Bunge.) on the growth of S. ltyphi bacteria. Experimental research with a completely randomized design, the results were analyzed using the One Way ANOVA test. Calamansi orange peel ethanol extract with concentrations of 0%, 5%, 7.5%, 10%, 12.5%, and 15% was tested for antibacterial activity against the growth of S. typhi bacteria using the disc diffusion method. The parameters observed were the diameter of the inhibition zone formed around the lpaper disc. The results of this study showed that ethanol extract of kalamansi orange peel (C. microcarpa Bunge.) had a significant effect on the growth of S. typhi bacteria, with a 95% confidence level and minimum inhibitory concentration (MIC) of ethanolic extract of kalamansi orange peel (C. microcarpa Bunge.) on bacterial growth. S. typhi was at a concentration of 10%, to be precise, MIC was at a concentration of 5% with an average inhibition zone diameter of 5.27 mm. The results of this study were donated in the form of student worksheets and related their role in life in the biology subject of SMA class X even semester